La responsabilidad civil de los médicos y la necesidad de la contratación de un seguro de responsabilidad profesional Iquitos 2021 - Valdez Marín, Rafael Augusto (2025)
This work is a thesis on the Civil Liability of Doctora and the Need to Contract Professional Liability Insurance. Iquitos – 2021; liability that occurs due to medical malpractice, whether due to negligence or incompetence; having analyzed previous works on the subject and verified the problem of the slowness of the payment of compensation to the injured parties and relatives in the event of death, we propose that doctors take out Professional Liability Insurance; for this we divided the work into the Theoretical Framework, Methodological Framework, Results and Discussion, Final Considerations and Recommendations, Bibliographic References and Annexes. We analyze the contracts between the patient and the doctor, the damage due to malpractice, whether due to incompetence or negligence, the compensation according to the current legislation, national and international, some specific cases at the national and local level, reaching the conclusion that it is necessary to have a regulation that obliges doctors to pay insurance for possible compensation if necessary. For this reason, a bill is proposed that seeks to repair in part, quickly, the damage caused to the patient or to his or her relatives, in the event of death.